Impact of align magnetic field on viscous flow with combined convective transport - Siti Farah Haryatie, Mohd Kanafiah; Abdul Rahman, Mohd Kasim; Nur Syamilah, Arifin; Syazwani, Zokri; Noor Amalina Nisa, Ariffin; Mohammed Al-Sharifi, Hussein Ali (Pushpa Publishing House, Prayagraj, India, 2021)
The present study focuses on the solution of the magnetic field that affected the flow of viscous fluid under combined convective transport. Flow is assumed to be moving over a stretching sheet with the Newtonian heating as the thermal condition. The mathematical model for present problem was derived from law of conservation of mass, the first law of thermodynamics and Navier Stokes equation. The formulation of the model is started by reducing the equations which were in partial differential equations to ordinary differential equation using the appropriate similarity transformations. The transformed equations were then solved by employing the finite difference scheme, known as Keller-Box method. The validation process is performed and found to be in excellent agreement with the existing results in the literature. The magnetic field that aligned 30° towards the flow boosted the value of skin friction up to 32.57% and 4.82% for Nusselt number compared to the magnetic field that acted transverse to the flow field (90°).